PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA APARATUR DI KECAMATAN MOJOLABAN KABUPATEN SUKOHARJO - Gusti Widayanti (Master of Public Administration, Universitas Slamet Riyadi, 2019)
The performance of the apparatus determines the quality of the servicesprovided. This study aims to describe the influence of leadership andmotivation on the performance of apparatus in Mojolaban sub-district,Sukoharjo Regency. The research method used to achieve the researchobjectives is a quantitative approach. Sampling in this study uses censusresearch, in this case the Apparatus of Mojolaban District numbered 34people, and 14 Village Heads. The total number of samples used is 48Apparatus. The results showed that leadership, motivation andperformance of the apparatus in Mojolaban Subdistrict, SukoharjoRegency were good. The results also show that leadership and motivationhave a positive effect on performance. leadership and motivation together(simultaneous) have a positive and significant effect on the performanceof the apparatus in Mojolaban Subdistrict, Sukoharjo Regency. thecontribution or influence given by the leadership and motivation variableson the performance of the apparatus in Mojolaban Subdistrict, SukoharjoRegency is 48.7% while the remaining 51.3% is influenced by otherfactors not examinedKeywords: Leadership, Motivation, Performance